APPRAISAL OF SOCIAL AND BEHAVIOR CHANGE COMMUNICATION IN THE FIGHT AGAINST INDISCRIMINATE WASTE DISPOSALS IN FEDERAL CAPITAL TERRITORY, ABUJA - FAGBAYIMU SAMSON ADEOLA; DESMOND ONYEMECHI OKOCHA (International Studies Journal)
Everyone has a responsibility to ensure environmental sustainability; both the government and the people have a part to play because issues affecting the government also impact the people. In the fight against careless garbage disposal in the Abuja Municipal Area Council, the Federal Capital Territory of Nigeria, Abuja, this study evaluates social and behaviour change communication. The purpose of this study was to find out how much the government has used social and behaviour change communication strategies in improving lives of the residents of Abuja Municipal Area Council as it concerns poor waste management and disposal practices. The social learning theory serves as the study's foundation while the survey design was adopted with structured questionnaire of (400) Abuja Municipal Area Council resident. The study revealed that people are aware of the improper disposal of various wastes, including leftover food, faeces, polythene, garment materials, and the like. Based on the findings, the study concludes that SBCC has demonstrated moderate effectiveness in promoting positive behaviour change however, awareness campaigns and the use of effective channel of communication in the subject matter are key in achieving this. The study therefore recommends that in order to maintain the wellbeing of the citizens or residents of Abuja Municipal Area Council, Abuja, as well as to make the local government neat and beautiful, the government should not only legislate but also execute or implement environmental policies, as well as create streets or locational waste collection bins and prosecute erring residents.